Quercetin Suppresses Human Glioblastoma Migration and Invasion via GSK3β/β-catenin/ZEB1 Signaling Pathway - Chen, Bo; Li, Xiaoli; Wu, Lihong; Zhou, Duanfang; Song, Yi; Zhang, Limei; Wu, Qiuya; He, Qichen; Wang, Gang; Liu, Xu; Hu, Hui; Zhou, Weiying (Frontiers in Pharmacology, 2022)
High invasiveness is a biological and clinical characteristic of glioblastoma and predicts poor prognosis of patients. Quercetin, a natural flavonoid compound, exhibits anticancer activity. However, we have a limited understanding of the possible underlying mechanism of quercetin in glioblastoma. In this study, we investigated the anticancer effect of quercetin in human glioblastoma cells. Our results showed that quercetin markedly suppressed the viability of glioblastoma cells in vitro and in vivo, and significantly inhibited glioblastoma cell migration and invasion. Moreover, quercetin reversed EMT-like mesenchymal phenotype and reduced the expression levels of EMT-related markers. Furthermore, we found that quercetin suppressed GSK-3β/β-catenin/ZEB1 signaling in glioblastoma. Taken together, our results demonstrate that quercetin inhibited migration and invasion of human glioma cells by suppressing GSK3β/β-catenin/ZEB1 signaling. Our study provides evidence that quercetin is a promising therapeutic natural compound to treat glioblastoma.